Morphological and Physiological Plasticity of Spinal Lamina II GABA Neurons Is Induced by Sciatic Nerve Chronic Constriction Injury in Mice - Zhang, Hongmei; Li, Yan; Yang, Qing; Liu, Xian-Guo; Dougherty, Patrick M. (Frontiers in Cellular Neuroscience, 2018)
Mice with transgenic insertion of code for enhanced green fluorescent protein (EGFP) at the locus for glutamic acid decarboxylase 67 (GAD67), one of two key enzymes for the synthesis of γ-aminobutyric acid (GABA) were used to test whether the morphological properties of these neurons show plasticity with nerve injury. Physiological properties and the delivery of intracellular label to EGFP-expressing lamina II neurons was done using whole-cell patch-clamp in spinal cord slices from sham and chronic constriction injury (CCI) mice. As well, whole cell recordings were made of non-EGFP labeled cells to ascertain changes in overall inhibitory signaling following CCI. The EGFP labeled neurons in both sham and CCI mice exhibited islet, central and vertical cell morphological profiles but no radial cell profiles were observed. The length of cell dendrites was found to be significantly shorter in CCI mice for all cell profile types. The longest neurites averaged 155.96 ± 18.29 μm in CCI mice compared to 334.93 ± 29.48 μm in sham control mice. No change was observed in either passive or evoked membrane properties of EGFP-expressing neurons in CCI versus sham mice. Meanwhile, the frequency of miniature inhibitory post-synaptic currents of non-EGFP expressing spinal lamina II neurons was significantly reduced. These results suggest that reduced inhibitory output from GABA neurons occurs with nerve injury in part due to altered cell morphology.